(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The literature of the past ten years (1980-1990) relative to juvenile hormones and their analogues has been considered by means of an examination of the principal entomological review publications (Review of applied Entomology, Ser. A e B, Entomology Abstracts, Apicultural Abstracts) as well as certain surveys (as issued in particular in Annual Review of Entomology), which provides a critical compendium. A historic outline of the identification of the glands and hormones of postembrionic development is traced, then the arguments into which research was carried out are examined, and particular mention is made of the various problems linking biochemical and physiological studies based on the practical applicatìon of hormone analogues for defence against harmful insects. Particular reference is made to Manduca sexta, Bombyx mori, Apis mellifera.